Composted sewage sludge and steel mill slag as potential amendments for urban soils involved in afforestation programs - Guerrini, Iraê Amaral [UNESP]; Croce, Ciro Guilherme Gentil [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Jacon, Camila Paula Rossetto Pescatori [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Ganga, Antonio; Capra, Gian Franco (Elsevier, 2017)
This study aimed to assess the impacts of composted sewage sludge and steel mill slag on urban soil fertility and tree growth. The research was conducted in an urban area (Botucatu, State of São Paulo, Brazil) characterised by extremely unfertile urban soils and with high production of these wastes. Plant growth, soil physico-chemical properties, and chemical composition of leafs were analysed during a 12-month field experiment. Principal factor analysis (PFA) and canonical correspondence analysis (CCA) were applied in the evaluation of the investigated soil-plant system. The results showed that soil fertility was increased by the combination of applied waste materials, which provided good conditions for full plant development and maintenance. PFA showed that the variability of the investigated model was mainly due to the role of soil organic matter as source/sink of soil heavy metals. CCA showed that the investigated soil-plant system was characterised by time-dependent evolution, with an equilibrium reached during the final stages, suggesting that the obtained results may be realistic from a long-term perspective. This study provides evidence that composted sewage sludge and steel mill slag are acceptable alternatives for improving urban soil quality and tree growth. The reuse of these wastes could provide a low-cost alternative for their complex and expensive management and disposal with, additionally, the possibility of turning currently bulky refuse material into a commodity.
Keywords: Composted sewage sludge; Steel mill slag; Urban afforestation; Urban soils